Long-Term Co-Circulation of Host-Specialist and Host-Generalist Lineages of Group B Streptococcus in Brazilian Dairy Cattle with Heterogeneous Antimicrobial Resistance Profiles - Oliveira, Laura Maria Andrade de; Simões, Leandro Correia; Crestani, Chiara; Costa, Natália Silva; Pantoja, José Carlos de Figueiredo [UNESP]; Rabello, Renata Fernandes; Teixeira, Lucia Martins; Khan, Uzma Basit; Bentley, Stephen; Jamrozy, Dorota; Pinto, Tatiana de Castro Abreu; Zadoks, Ruth N. (MDPI, 2024)
Group B Streptococcus (GBS) is a major cause of contagious bovine mastitis (CBM) in Brazil. The GBS population is composed of host-generalist and host-specialist lineages, which may differ in antimicrobial resistance (AMR) and zoonotic potential, and the surveillance of bovine GBS is crucial to developing effective CBM control and prevention measures. Here, we investigated bovine GBS isolates (n = 156) collected in Brazil between 1987 and 2021 using phenotypic testing and whole-genome sequencing to uncover the molecular epidemiology of bovine GBS. Clonal complex (CC) 61/67 was the predominant clade in the 20th century; however, it was replaced by CC91, with which it shares a most common recent ancestor, in the 21st century, despite the higher prevalence of AMR in CC61/67 than in CC91, and high selection pressure for AMR from indiscriminate antimicrobial use in the Brazilian dairy industry. CC103 also emerged as a dominant CC in the 21st century, and a considerable proportion of herds had two or more GBS strains, suggesting poor biosecurity and within-herd evolution due to the chronic nature of CBM problems. The majority of bovine GBS belonged to serotype Ia or III, which was strongly correlated with CCs. Ninety-three isolates were resistant to tetracycline (≥8 μg/mL; tetO = 57, tetM = 34 or both = 2) and forty-four were resistant to erythromycin (2.0 to >4 μg/mL; ermA = 1, ermB = 38, mechanism unidentified n = 5). Only three isolates were non-susceptible to penicillin (≥8.0 μg/mL), providing opportunities for improved antimicrobial stewardship through the use of narrow-spectrum antimicrobials for the treatment of dairy cattle. The common bovine GBS clades detected in this study have rarely been reported in humans, suggesting limited risk of interspecies transmission of GBS in Brazil. This study provides new data to support improvements to CBM and AMR control, bovine GBS vaccine design, and the management of public health risks posed by bovine GBS in Brazil.
Keywords: antimicrobial resistance; bovine mastitis; dairy cattle; group B Streptococcus; molecular epidemiology